Pembinaan Hukum tentang Pemahaman Pancasila Sebagai Ideologi Negara pada Santri Pesanteren Miftahul Huda dan Generasi Muda RT 002 RW 005 Kelurahan Sembulang Kecamatan Galang Kota Batam - Ukas, Ukas; Jamba, Padrisan; Abbas, Azhar (Prosiding, 2024)
Pancasila as the ideology of the nation embodies positive values for the life of the beloved Indonesian people, values that align with the law, the 1945 Constitution, and 'Bhineka Tunggal Ika' (Unity in Diversity). In the governance of national life based on Pancasila as an ideology, it emphasizes togetherness and unity in the societal values, combating ideologies that contradict Pancasila. Therefore, it is necessary to socialize Pancasila values as a means of preserving these values. The current rise of radicalism needs vigilance against its influence, especially among the younger generation including those in Islamic boarding schools ('pesantren'), an obligation to instill the entirety of Pancasila values, especially among the youth. In national and state life, togetherness and unity as stated in Pancasila values are absolute principles that must be adhered to by the younger generation as well as responsible citizens across all segments of society. Misguided ideologies such as radicalism should be combated, similar to practices in other countries, whether under Continental European legal systems or other legal frameworks, which always prioritize their positive legal principles in adopting a nation's ideology